2011
DOI: 10.1007/s00586-011-2064-3
|View full text |Cite
|
Sign up to set email alerts
|

Syrinx resolution after posterior fossa decompression in patients with scoliosis secondary to Chiari malformation type I

Abstract: Introduction Description of syrinx resolution after posterior fossa decompression (PFD) in patients with scoliosis secondary to Chiari malformation type I (CMI) and syringomyelia (SM) has been rarely reported in the literature. This study was performed to investigate the outcome of PFD in patients with scoliosis secondary to CMI and to identify potential predictive factors for better outcome after PFD. Material and methods Patients with scoliosis secondary to CMI and SM, who had undergone PFD during the period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 30 publications
(43 reference statements)
0
25
0
6
Order By: Relevance
“…Similar to other studies, the majorities of the abnormalities in our series were Chiari 1 malformation or syringomyelia or combined. Previous studies have demonstrated that a large proportion of patients with Chiari 1 malformation or syringomyelia have no other clinical symptom except scoliosis [24,25]. Sexual dimorphism was one of the significant features of IS, and considered to be related to the etiopathogenesis of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies, the majorities of the abnormalities in our series were Chiari 1 malformation or syringomyelia or combined. Previous studies have demonstrated that a large proportion of patients with Chiari 1 malformation or syringomyelia have no other clinical symptom except scoliosis [24,25]. Sexual dimorphism was one of the significant features of IS, and considered to be related to the etiopathogenesis of AIS.…”
Section: Discussionmentioning
confidence: 99%
“…While sex, age, duration of followup, tonsillar and syrinx characteristics, [21][22][23]32 and pB-C2 distance 17 have been demonstrated to be associated with syrinx resolution in some studies, 1 study considered multiple variables 30 and found none to be associated with radiological outcome. The results with regard to clinical outcomes have been similarly diverse, with variables like 4 and spinal cord diameter 9 established as being correlated with outcomes.…”
Section: Predictive Variables Identified In Previous CMI Studiesmentioning
confidence: 99%
“…One study by Wu and colleagues of 44 pediatric patients undergoing dural opening PFD for CM-I, syrinx, and scoliosis reported syrinx improvement in 82% of patients by 6 months postoperatively, and in 98% of patients over the course of follow-up. 48 Wetjen and colleagues studied 29 adult patients with CM-I and syrinx after dural opening PFD and found the median time from surgery to greater than 50% reduction in syrinx size to be 3.6 months with a mean of 6.5 months. 46 By 6 months, 86% of patients had demonstrated radiographic improvement, and all 29 patients demonstrated radiographic improvement during their follow-up.…”
Section: Discussionmentioning
confidence: 99%